THE INFLUENCE OF A PROBLEM-BASED LEARNING MODEL ASSISTED BY SPIN WHEEL MEDIA ON THE CONCEPTUAL UNDERSTANDING ABILITY OF CLASS IV PRIMARY STUDENTS IN THE ENERGY SOURCES MATERIAL - Didik Triyadi; Sumarli Sumarli; Citra Utami (Universitas Negeri Surabaya in collaboration with Perkumpulan Pendidik IPA Indonesia (PPII), 2024)
This research aimed to (1) know the differences in conceptual understanding between students using a Problem-Based Learning (PBL) model assisted by spinning wheel media and students using the conventional method in energy resources material, (2) describe the influence of the PBL model assisted by Spin Wheel media 4th-grade elementary school students on the conceptual understanding ability of energy sources, and (3) describe students' responses on the implementation PBL model assisted by Spin Wheel media on energy source material. The type of research used was quasi-experimental research with a quantitative approach. The population in this study was all class IV students, totalling 57 students. Sampling used a total sampling technique. The sample selected in this research was class IV B students, totalling 29 students in the experimental class and 28 class IV A students in the control class. The instruments used in this research were conceptual understanding ability test sheets and student response questionnaires. The data analysis technique used a two-independent sample t-test, effect size, and percentage of student response questionnaires. The results of the research showed that (1) there was a difference in the conceptual understanding ability of students who used the PBL model assisted by Spin Wheel media with students who used the conventional method on energy source material with the result tcount > ttable = 3.5146 > 2.004, (2) the PBL model assisted by Spin Wheel media had a high influence on the conceptual understanding fourth-grade students on energy sources material with an effect size result of 0.967; (3) students response were positive to PBL model assisted by Spin Wheel media with a percentage of 93% in the very high category. So, the results from this study can be concluded that there was an influence of the PBL model assisted by Spin Wheel media on students' conceptual understanding ability on energy sources material.